Rites of Passage: Liminality in Not-for-Profit Leadership Transitions from Western Expatriate Subsidiary Founders to Emerging Non-Western National Leaders - Porter, Lloyd Philip (Curtin University, 2023)
This qualitative study examined three leadership transitions in one international not-for-profit organisation. The study utilised van Gennep’s concept of liminality as a frame of reference to understand how Western expatriate founders, emerging non-Western National successors, and selected stakeholders experience leadership transition. The three case studies examined the main sources of tension, how organisational practices affect the selected stakeholders, and provided an understanding of the challenges involved in leadership transitions within this context.